Aplicación de Incoterms en la exportación de combustibles y productos de las industrias extractivas en Colombia durante la presente década (2019)
The purpose of this monograph is to analyze the application of Incoterms in the export of fuels and products of extractive industries in Colombia during this decade. For the development of this research, each of the Incoterms in force since 2010 was identified, which is the last update made, specifying the risks and responsibilities of each one.